Current perspectives on postoperative cognitive dysfunction in geriatric patients: insights from clinical practice - Zhang, Liang; Qiu, Yi; Zhang, Zhi-feng; Zhao, Yi-fan; Ding, Yu-mei (Frontiers in Medicine, 2024)
Postoperative cognitive dysfunction (POCD) is a common and serious postoperative complication in elderly patients, affecting cognitive function and quality of life. Its pathophysiology is complex, involving age-related cognitive decline, surgical and anesthetic factors, systemic and neuroinflammation, as well as genetic and environmental contributors. Comprehensive preoperative assessment and optimization, the selection of appropriate anesthetic agents, minimally invasive surgical techniques, and early postoperative rehabilitation and cognitive training are effective strategies to reduce the incidence of POCD. Recent research suggests that anti-inflammatory drugs and neuroprotective agents may be promising in preventing POCD. Additionally, non-pharmacological interventions, including cognitive and physical training, have shown positive effects. Future research directions should include large-scale clinical trials and mechanistic studies to further understand and manage POCD, along with integrating new findings into clinical practice. Continuous education and training for healthcare professionals are essential to ensure the effective application of the latest research findings in patient care. Through multidisciplinary collaboration and ongoing improvements, these efforts can significantly enhance the cognitive function and quality of life of elderly surgical patients.